Structural and Mineral Exploration Study at Transition Zone of Mambilla Plateau and Environs, Northeastern Nigeria, Using Integrated Geophysical Data (Journal of Pure and Applied Sciences (Science Forum), 2025)
To figure out the underground structures, the tectonic framework, and the mineralsin the area., the transition zone of the Mambila Plateau and surroundings innortheastern Nigeria has been explored utilizing aeromagnetic, pseudo gravity, andlandsat-8 remotely sensed. Several depth estimation and filtering methods, such asthe first vertical derivative, total horizontal derivative, and total gradient, were usedon the magnetic data (analytical signal), upward continuation, and pseudo gravitytransform. Using landsat-8 imagery data, aeromagnetic, and pseudo gravitytransforms, it was possible to identify mineral zones with hydrothermal changes,shallow and deep intrusive masses, buried faults, lineaments, and lithological units.A thorough field mapping revealed and confirmed a few mineralization zones withgreat potential. The mining areas exhibit high structural density, which highlightsthe value of lineaments density maps in identifying probable mineralization zonesand the structures that regulate mineralization. The principal tectonic trends areNE-SW, NNE-SSW along with less significant NNW, WNW, NS, and NE trends, isshown by statistical trend analysis of the lineaments collected from geological,filtered magnetic, and density maps. The corresponding magnetic structures werescanned upward continuing at depths ranging from the surface to 3000m. Powerspectrum and source parameter imaging approaches have been used to determinethe depth of a structure. The results reveal that the average computed depth rangesfrom 1.2 km to 1.7 km, whereas the depth to volcanic intrusions ranges from 0.345km to 0.461 km